An Analysis on the Students’ Speaking Skill in Online Class - Siti Nafisatul Hikmah; Lusi Marleni (Journal of Innovative and Creativity, 2021)
Analysis of students 'speaking skills in this study aims to determine how students' speaking skills using WhatsApp. The Students have difficulty expressing ideas of the students having difficulty speaking. This research was conducted in class X MIPA and IIS in 2019/2020. As a research subject, online learning involved 40 class X students. The design and method used in this study was descriptive research. The author uses the test as an instrument in this study. The results of this study indicate that the mean score of the students is 70.3 which indicates that the students' speaking skills are good. Students can speak English and understand what is being said, Students also feel confident when speaking English. Meanwhile 11 or 25.1% of students did not like learning English, especially speaking skills. Students did not speak English and did not understand what was said. This means that the speaking ability of students in this class is good.